Isolasi, Identifikasi, dan Uji Aktivitas Antibakteri Fungi Endofit Daun Alpukat (Persea Americana Mill) Terhadap Pseudomonas aeruginosa dan Staphylococcus aureus - Zamra Hairani; St. Ratnah; Sesilia Rante Pakadang (Jurnal Mandala Pharmacon Indonesia, 2023)
Avocado (Persea americana Mill) is a plant that contains antibacterial substances, especially in its leaves. Flavonoids, saponins and alkaloids are active compounds in avocado leaves which can prevent some bacterial growth. This study aims to isolate, identify and determine the antibacterial activity of avocado leaf endophytic fungal isolates growing P. aeruginosa and S. aureus. This type of research, namely experimental research, isolates endophytic fungi using avocado leaves inoculated on PDA media which has been added with 0.005% chloramphenicol in a petri dish and incubated at a temperature of 25oC for 5-7 days. Antibacterial activity was tested using a paper disk with the agar diffusion method. This research showed that young avocado leaves produced 3 isolates, namely isolate 1 was suspected to be Trichoderma sp., isolate 2 was suspected to be Rhizoctonia sp., and isolate 3 was suspected to be Fusarium sp. From the results obtained, it was concluded that the endophytic fungi of avocado leaves from isolate 2, and isolate 3 provided an inhibition zone against P. aeruginosa and isolate 1, and isolate 3 provided an inhibition zone against S. aureus.